Analysis on micro-motion of cylinder block based on elasto-hydrodynamic lubrication. Issue 5 (9th December 2019) - Jiang, Jihai; Yan, Wei-Peng; Li, Ge-Qiang
Abstract : Purpose: The purpose of this paper is to analyze the micro-motion of the cylinder block. Design/methodology/approach: Based on the elasto-hydrodynamic lubrication, a numerical model for the cylinder block/valve plate interface is proposed, with consideration of the elastic deformations, the pressure-viscosity effect and asperity contacts. The influence-function method is applied to calculating the actual deformations of the cylinder block and the valve plate. The asperity contact model simplified from Greenwood assumption is introduced into the numerical model. Furthermore, the relationship between the micro-motion and the operating condition, the sealing belt width is discussed, respectively. Findings: The results show an increase in the discharge pressure causes the tilt state and the vibrating motion getting worse, which can be eased by improving the rotational speed, the sealing belt width and the ratio of external and internal sealing belt width. Originality/value: The proposed research can provide a theoretical reference for the optimizing design of cylinder block/valve plate pair.